Thematic Progression in Students’ Descriptive Texts - Pangestu, Galih; Harvian, Ervina Dwita; Suprijadi, Dasep (PROJECT (Professional Journal of English Education), 2019)
Thematic progression is important in coherence to be considered as good text. So, it needs the element of thematic progression or it can be called theme and rheme. Theme and rheme constitutes the main part of clause, because comprehending the thematic progression may help to understand whole clause.  The coherence text should also be necessary written by students in senior high school in Batujajar. This investigation is conducted to consider the thematic progression and coherence in descriptive text. The purpose of this research is to identify types of thematic progression in students’ descriptive text and the levels of coherence in students’ descriptive text. The researchers use descriptive quantitative method.. The data are all clauses from paragraphs on text. The result of the result shows that there are two of three models of thematic progression found, namely zig-zag theme and re-iteretion. In addition, the finding also found that  there are three level coherence in every students’ descriptive text such as a good, fair, and less levels coherence.